TINJAUAN LITERATUR SISTEMATIS HAMBATAN ADMINISTRASI KEPENDUDUKAN TERHADAP PERILAKU PEMENUHAN PENGOBATAN ANAK JALANAN DALAM KERANGKA HIERARKI KEBUTUHAN MASLOW - Dhepita Septiyani; Hastin Trustisari (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
Street children are a marginalized population group with high morbidity rates but very low access to healthcare. Although they are vulnerable to malnutrition and skin infections, the majority of street children exhibit poor health-seeking behavior, tending to rest at home rather than seek professional medical help. The purpose of this systematic literature review is to analyze structural barriers in the form of population administration on the treatment-seeking behavior of street children through the perspective of Maslow's Hierarchy of Needs Theory. This study uses the Systematic Literature Review method. The literature identification process was conducted through academic databases covering the period 2016–2025 using Publish or Perish software. Article selection was carried out using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses protocol, resulting in 18 selected journals for synthesis. The findings show that the absence of identity documents such as a Population Registration Number/Family Card is a major obstacle in accessing BPJS Health and public facilities. Theoretically, the failure to fulfill the need for security in population administration at the second level of Maslow's Hierarchy results in the obstruction of fulfilling physiological needs in the form of medical treatment at the first level. This is exacerbated by psychosocial factors such as trust issues towards health authorities. In conclusion, there is a significant influence between population administration barriers and poor treatment behavior among street children.